Oxygenation Monitoring With A Ventilator In An Intracerebral Hemorrhage Patient In The Intensive Care Unit - Fuziananto, Erwin; Ramdani, Wawan Febri (ProNers, 2026)
Background: Intracerebral hemorrhage (ICH) is a neurological emergency with a high risk of causing secondary brain injury due to hypoxia and impaired ventilation. Oxygenation with mechanical ventilation is an important part of intensive nursing care to maintain oxygenation and cerebral tissue perfusion. Objective: To analyse the role of oxygenation with a ventilator in the nursing care of patients with intracerebral hemorrhage in the intensive care unit (ICU). Methods: This report is a descriptive case report, prepared in accordance with the CARE (CAse REport) guideline. The subject was one patient with a diagnosis of intracerebral hemorrhage treated in the ICU. Data were collected through nursing observation, a vital-signs monitoring sheet, and documentation of medical and nursing therapy during care. Data were analysed descriptively by relating clinical findings and nursing interventions to the literature. Results: Monitoring showed that, during a course that also included craniotomy, tracheostomy, and pharmacotherapy, the patient’s respiratory and hemodynamic status remained relatively stable. During care, no signs of severe hypoxia were found, and the patient’s condition was relatively stable with close monitoring. Conclusion: In this single case, oxygenation with a ventilator was an important component of intensive nursing care, delivered alongside concurrent surgical and pharmacological management; because it was one patient, the specific contribution of the ventilator or of nursing care cannot be isolated.